Pengaruh Model Pembelajaran Kooperatif Tipe STAD Berbasis Media Animasi Dan Kemampuan Awal Terhadap Pemahaman Konsep Listrik Dinamis Siswa SMA Negeri 8 Palu - Wahyuni N. Laratu; Darsikin Darsikin; Unggul Wahyono (Universitas Tadulako, 2016)
Physics as a subject of the natural phenomenon is expected to be taught in a simplistic so the learning model and media are used by teachers greatly affect students' understanding of a concept. This study aimed to describe:(1) the effect of the initial capabilities of the students' understanding of concepts in a dynamic electrical material. (2) the effect of learning model for understanding the concept. (3) identify the interaction between the initial capabilities and learning model for understanding the concept. The population in this study were all students of class X of SMAN 8 Palu academic year 2013/2014, amounting to 103 students. Data collection techniques with a random sample, and the test in the form of multiple choice. The tests are given to measure students' understanding of physics concepts. Data analysis technique used was qualitative quai experiment with a 2x2 factorial design. The results showed that: (1) The initial capability significantly affect students' understanding of the concept. (2) the learning STAD significantly affect students' understanding of the concept. (3) there is no interaction between prior knowledge and understanding of the concept of students' learning model.